2, 3′, 4, 4′, 5-Pentachlorobiphenyl impairs insulin-induced NO production partly through excessive ROS production in endothelial cells. (13th October 2017) - Long, Yang; Huang, Can; Wu, Jian; Cheng, Jin-nan; Liang, Guan-nan; Jiang, Chun-xia; Wan, Qin
Abstract: Polychlorinated biphenyls (PCBs) have been reported to be associated with increased risk to hypertension, atherosclerosis, cardiovascular disease, etc. 2, 3′, 4, 4′, 5-Pentachlorobiphenyl, known as PCB-118, is a member of coplanar PCBs which renders their structure similar to polychlorinated dibenzo- p -dioxins (PCDDs) and has dioxin-like activity. In our current study, we investigated the effect of PCB-118 exposure on nitric oxide (NO) production and the underlying mechanisms in vitro . Exposure of PCB-118 impaired insulin-induced NO production and endothelial nitric oxide synthase (eNOS) activity in human umbilical vein endothelial cells (HUVECs) with no significant effect on cell viability. Furthermore, PCB-118 treatment induced oxidative stress. In addition, scavenging of reactive oxygen species (ROS) by 10 μM N -acetyl-l -cysteine (NAC) partly rescued impaired insulin-induced eNOS activities and NO productions induced by PCB-118 in HUVECs. Taken together, these results indicate that PCB-118 mediates lower eNOS activity and impairs insulin-induced NO production partly through excessive ROS production in endothelial cells.